Nuclear response using correlated realistic interactions: first-order random phase approximation and beyond - Papakonstantinou, P.; Roth, R.; Paar, N. (HNPS Advances in Nuclear Physics, 2020)
A correlated realistic interaction derived within the Unitary Correlation Operator Method (UCOM) based on the Argonne V18 nucleon-nucleon potential is used in calculations of nuclear response for closed-shell nuclei. Giant resonances are examined in the framework of the random-phase approximation (RPA). The effects of explicit ground-state correla- tions and of higher than first-order configurations are discussed.